Designing road safety interventions for young drivers – The power of peer influence. (May 2018) - Weston, Lauren; Hellier, Elizabeth
Highlights: Young drivers made more violations to attain social prestige from their peers. A peer-to-peer intervention group stated safer attitudes and intentions at follow-up. The results support use of peer education tools in young driver safety interventions. Abstract: Peer passengers are associated with risky driving behaviour and increased collision rate in young drivers, but the mechanism by which young drivers are influenced by their peers is not well understood. Here we report two studies that explore the effect of peer influence on young drivers. The first explored the relationship between susceptibility to peer influence and young drivers' engagement in risky driving behaviour. 163 young drivers completed self-report measures of risky driving behaviour and susceptibility to different forms of peer influence. Results showed that young drivers who were influenced by their peers to attain social prestige and through peers intervening in their decisions committed more driving violations. The second study sought to utilise the susceptibility of young drivers to peer influence by using peers to design and deliver a safety intervention, following the 'U in the Driver Seat' model from the US. When compared to a traditional fear appeal and a control, the peer intervention group reported safer attitudes and intentions to drive safely at follow-up. Together these studies provide insight into how peers influence young drivers' risky behaviour, and support the notion of using peer education tools in young driver safety interventions.